A Multivariate Posterior Odds Approach to Assessing Competing Exchange Rate Models - Fuhrer, Jeffrey C.; Weiller, Kenneth J. (The Review of Economics and Statistics, 1991)
Jeffrey C. Fuhrer, Kenneth J. Weiller, A Multivariate Posterior Odds Approach to Assessing Competing Exchange Rate Models, The Review of Economics and Statistics, Vol. 73, No. 1 (Feb., 1991), pp. 113-124